Experimental Investigation of Rotor-Stator Interaction in Axial-Flow Turbines and Compressors - Heinz E. Gallus (International Journal of Rotating Machinery)
Detailed results of unsteady flow measurements in a stator-rotor-stator assembly of an axial-flow turbine as well as an inlet guide vane-rotor-stator formation of an axial-flow compressor are presented in this paper.